2021
DOI: 10.3390/f12111571
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Impact of a Mass Timber Building—A Case Study

Abstract: The study focuses on a life cycle assessment of a wood-based residential building and evaluates the magnitude of individual construction components—foundations, flooring, peripheral wall, inner walls, ceiling, roof, windows, and doors—in terms of climate change; acidification; eutrophication; photochemical oxidation; depletion of abiotic elements and fossil fuels; and water scarcity categories within the system boundaries of the Product stage of the life cycle. The assessment was done using the SimaPro softwar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…It is important to note that early LCAs may be less accurate as they are limited to predictive estimates, since design details material selections are subject to significant change as various disciplines work together on a design. Another strategy for LCA and by far the most common is including a full analysis after design completion (table 1-'Design completion') as a post-design calculation report or conclusion [22][23][24][25][26][27]. Recent literature review of LCA in design revealed that most LCAs are reactive (after design completion), but that proactive methods have better potential to effect actual change, a factor acknowledged by those innovating in LCA capabilities for early design [34][35][36].…”
Section: Lca In the Design Processmentioning
confidence: 99%
“…It is important to note that early LCAs may be less accurate as they are limited to predictive estimates, since design details material selections are subject to significant change as various disciplines work together on a design. Another strategy for LCA and by far the most common is including a full analysis after design completion (table 1-'Design completion') as a post-design calculation report or conclusion [22][23][24][25][26][27]. Recent literature review of LCA in design revealed that most LCAs are reactive (after design completion), but that proactive methods have better potential to effect actual change, a factor acknowledged by those innovating in LCA capabilities for early design [34][35][36].…”
Section: Lca In the Design Processmentioning
confidence: 99%
“…When compared with concrete constructions, CLT constructions have a lower thermal conductivity coefficient with the same thickness [ 5 , 6 ]. In addition, there are some other advantages of CLT construction including faster on-site construction times, lighter weight materials, use of a sustainable natural resource, carbon sequestration, lower embodied energy, and lower greenhouse gas emissions [ 7 , 8 , 9 ]. For these reasons, CLT elements have been successfully used in multi-storey timber-based structures.…”
Section: Introductionmentioning
confidence: 99%